Parametric Study of Seismic Performance of Steel Bridges Pier Rehabilitated with Composite Connection - Rohola Rahnavard (Iranian Society of Structrual Engineering (ISSE), 2019)
Connections pipe pile to cap beam in steel bridges have important roles on structure strength affecting lateral loads such as earthquake. One of the most important strategies are to translate plastic hinge from connections to the other places in structure. In this study four types of composite steel connections and a direct welded connection modeled and analyzed in finite element ABAQUS software. After verification of the real model using available experimental data, the other models are made. The models under cyclic loading protocol SAC was analyzed and the results were compared. The results of this study indicated that the using composite connections, increased shear capacity and improved its performance. In addition, the obtain results show that infill concrete strenght doesn’t have effects on shear capacity and ductility of steel bridge. The results indicated that using composite connection between pipe pile and cap beam translate plastic hinge from connection to pile area. Also, the results show that increasing composite length improved the ductility of total steel bridges. Also, regarding to results of this study, it seen that buckling in model with welded connection occur on surface between pipe pile and cap beam. However, in the models with composite connections the buckling translated from connection to pile area.